Problemas para tragar y el adulto mayor - Wendy J. Dahl (EDIS)
A swallowing problem may be a serious health issue for an older adult. This 3-page Spanish-language fact sheet describes common reasons for problems chewing and swallowing, why this is a concern, and where to get more information. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.